KUALITAS PRODUK, CITRA MEREK DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN ONLINE (PENGGUNA SHOPEE DI SURAKARTA) - Muhammad Irvan; Burhanudin Ahmad Yani; Fithri Setya Marwati (ITB AAS INDONESIA Surakarta, 2022)
This research was conduted with the aim to analyze the influence of product quality, brand image and brand equity on online purchasing descisions (shopee users in Surakarta). This study uses quantitative deskritive sampling techniques using saltdental sampling methods. Data collection is done with observas, and kuisoner techniques. The population in this study is infinite. The sample in the study was 100 peoples. Data analysis uses classical assumptions and multiple linear regression analysis. The results showed that product quality, brand image and brand equity influence postively and significantly on online purchasing decisions (shopee users in Surakarta). Keywords: Purchasing Decisions, Product Quality, Brand Image and Brand Equity